Systematic Literature Review Filsafat Pendidikan Dalam Pembentukan Karakter Siswa - Junaharesdi, Aldo (Yayasan Sembilan Pemuda Indonesia, 2025)
This article discusses the importance of philosophical foundations in education, especially in the context of student character building. Through a qualitative approach with a systematic literature review (SLR) method, this research explores various schools of educational philosophy, focusing on realism and idealism. It is emphasized that education cannot be viewed holistically without a deep philosophical understanding. Pancasila as the national philosophy of education is the main reference in the implementation of education in Indonesia. The article also highlights the challenges of implementing idealism in educational curricula and practices and the need for further research to understand the effectiveness of this approach in various cultural contexts. The emphasis on universal values and absolute truth in idealism education is expected to strengthen students’ character.